1983
DOI: 10.1128/mcb.3.4.720
|View full text |Cite
|
Sign up to set email alerts
|

Regular arrangement of nucleosomes on 5S rRNA genes in Xenopus laevis.

Abstract: The chromatin structure of the oocyte-type 5S RNA genes in Xenopus laevis was investigated. Blot hybridization analysis of DNA from micrococcal nuclease digests of erythrocyte nuclei showed that 5S DNA has the same average nucleosome repeat length, 192 ± 4 base pairs, as two Xenopus satellite DNAs and bulk erythrocyte chromatin. The positions of nuclease-sensitive regions in the 5S DNA repeats of purified DNA and chromatin from erythrocytes were mapped by using an indirect end-labeling technique. Although most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 53 publications
6
23
0
Order By: Relevance
“…Earlier work had demonstrated that removal of histone H1 was all that was required for transcription factors to activate the oocyte 5S rRNA genes in somatic nuclei (12,76). The in vitro positioning that we obtain in the presence of histone H1 on the oocyte 5S rRNA genes is consistent with the low-resolution in vivo mapping on nucleosomes on these repeats in the chromosome of somatic cells (12,29,119). In our earlier studies, we concluded that the addition of histone H1 directed the positioning of a nucleosome over the oocyte 5S rRNA gene (12).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Earlier work had demonstrated that removal of histone H1 was all that was required for transcription factors to activate the oocyte 5S rRNA genes in somatic nuclei (12,76). The in vitro positioning that we obtain in the presence of histone H1 on the oocyte 5S rRNA genes is consistent with the low-resolution in vivo mapping on nucleosomes on these repeats in the chromosome of somatic cells (12,29,119). In our earlier studies, we concluded that the addition of histone H1 directed the positioning of a nucleosome over the oocyte 5S rRNA gene (12).…”
Section: Discussionsupporting
confidence: 71%
“…4) (34,36,66). Even though our experiments employ a single nucleosome, the key binding sites (ϩ81 to ϩ91) for TFIIIA would be predicted to remain accessible within the 40-to 50-bp linker DNA present in the somatic 5S rRNA gene nucleosomal repeat (119). A final point is histone H1 binds selectively to nucleosomal DNA compared to naked DNA (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Removal of histone H1 from somatic cell chromatin allows transcription factors to gain access to the oocyte type 5S rRNA genes. The oocyte 5S rRNA genes in somatic cells in vivo are known to be packaged into nucleosomes (Gottesfeld and Bloomer 1980;Young and Carroll 1983) and the positioning of histone-DNA contacts appears dependent on histone H1 (Chipev and Wolffe 1992). Sliding of nucleosomes following H1 removal may allow transcription factors access to the oocyte 5S rRNA genes.…”
Section: Histone H1 and The Selective Repression Of The Oocyte 5s Rrnmentioning
confidence: 99%
“…2B} for both templates. Nucleosomes are assembled with a physiological spacing of -180-190 bp (Young and Carroll 1983). No major changes in chromatin organization occur between 4 and 16 hr, although large differences in transcriptional activity occur between initially single-or double-stranded templates over this time interval {see Fig.…”
Section: Chromatin Assembly On Replicating Single-stranded and Nonrepmentioning
confidence: 99%